Thermal conductivity optimization and entropy generation analysis of titanium dioxide nanofluid in evacuated tube solar collector - Gan, Yong Yang; Ong, Hwai Chyuan; Ling, Tau Chuan; Zulkifli, Nurin Wahidah Mohd; Wang, Chin Tsan; Yang, Yung Chin (Elsevier, 2018)
Titanium dioxide (TiO2) nanofluid is produced by dispersing a small amount of TiO2 nanoparticles in distilled water. The high thermal conductivity of the TiO2 nanofluid can improve the performance of evacuated tube solar thermal collector (ETSC). The main objectives of this study are to evaluate the thermal efficiency and perform entropy analysis of an ETSC in which TiO2 nanofluid is used as the working fluid. Response surface methodology is used to determine the optimum thermal conductivity of the TiO2 nanofluid. The following factors are varied for the optimization process: (1) volumetric concentration of nanoparticles, (2) amount of surfactant, and (3) sonication time. The optimum factors are as follows: (1) volumetric concentration of TiO2 nanoparticles: 0.50 vol%, (2) surfactant-to-nanoparticle ratio: 1:1, and (3) sonication time: 10.0 min. Excessive amounts of polyvinylpyrrolidone (PVP) surfactant significantly reduce the thermal conductivity of the TiO2 nanofluid. The thermal conductivity of the TiO2 nanofluid increases by 7.28% when it is prepared under optimum conditions. The TiO2 nanofluid with the optimum thermal conductivity is used as the working fluid in the ETSC. It is found that thermal efficiency of the ETSC increases with an increase in the mass flow rate of water and TiO2 nanofluid. The results show that the entropy generation decreases by 1.23% whereas the thermal efficiency increases by 16.5% when the optimum TiO2 nanofluid is used in the ETSC compared with those for distilled water at a mass flow rate of 0.033 kg/s. The heat transfer capability increases by using TiO2 nanofluid with high thermal conductivity as well as high mass flow rate. In conclusion, the performance of the ETSC can be enhanced by using stable nanofluid as the heat transfer fluid because of its high thermal conductivity.